Pinocchio - Zamorsky, Tania; Collodi, Carlo, 1826-1890.; Corvino, Lucy (New York : Sterling, 2008)
A retelling of the classic children's story of Pinocchio, a little wooden puppet who desires to become a real boy.
4.7
3-6
3-6
Keywords: Fairy tales; Puppets -- Juvenile fiction; Fairy tales; Puppets -- Fiction; Fairy tales; Puppets and puppet plays -- Fiction